Depression and its associated factors among pregnant women in central Vietnam. Issue 1 (January 2021) - Luong-Thanh, Bao-Yen; Nguyen, Lan Hoang; Murray, Linda; Eisner, Manuel; Valdebenito, Sara; Hoang, Tuyen Dinh; Phuc Do, Huyen; Vo, Thang Van
To date, little attention has been given to prenatal depression, especially in low and middle-income countries. The aim of this research was to assess the prevalence of depression and its associated factors amongst pregnant women in a central Vietnamese city. This cross-sectional study included 150 pregnant women from 29 to 40 weeks of gestation, from eight wards of Hue city, via quota sampling from February to May 2019. We employed the Patient Health Questionnaire (PHQ-9) to assess depression. Findings suggest the need to provide routine screening of pregnant women in primary care for depressive symptoms and other mental health problems.